Digital Identities and Aesthetic Expression: Uncovering Young Indonesians Argumentation in Filter Usage on Social Media - Triantoro, Dony Arung; Pramana, M. Agung (Universitas Ahmad Dahlan, 2024)
This study delves into the diverse motivations and impacts of Instagram filter usage among young Indonesians, focusing on how these digital tools influence selfrepresentation and social interaction within the digital sphere. While Instagram filters are traditionally viewed as aesthetic enhancements, this research highlights their broader roles, including entertainment, education, and personal branding. Utilizing a qualitative approach, this paper collects data through interviews and netnography, employing snowball sampling to gather in-depth insights from eight young Instagram users. Findings indicate that young people use filters not only for visual enhancement but also for fun, educational engagement, and the expression of personal traits like humor and intelligence. This usage underscores young people's agency as active consumers, manipulating digital tools to craft their public personas and navigate social media spaces. This study underscores the need for further quantitative research to explore the widespread patterns of filter consumption among youth, aiming to enrich the understanding of digital identity formation in a globalized context.